Analisis Terhadap Perlindungan Perempuan Korban Kekerasan Seksual Dari Segi Hak Asasi Manusia Dalam Sistem Hukum Positif Indonesia - Windy Claudia Yunus; Leni Dwi Nurmala; Robby Waluyo Amu; Roy Marthen Moonti (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The aim of the research is to determine and analyze the concept of protecting women victims of sexual violence in terms of human rights in Indonesia's positive legal system. And to find out and analyze the form of state responsibility in protecting women victims of sexual violence in terms of human rights in Indonesia's positive legal system. The type of research, namely Normative Juridical, is legal research that places law as a building system of norms. The legal materials used in this research come from primary legal materials obtained directly from legal materials, both primary legal materials and secondary legal materials. In this case the author will try to collect information that is relevant to the topic or problem being researched, as well as examine in depth the information collected and synchronize it with the main problem in this thesis. The concept of protecting women victims of sexual violence in terms of human rights in Indonesia's positive legal system is that victims have the right to obtain their rights which are generally regulated in Article 5 of Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection. Witnesses and victims also have the right to receive medical assistance, rehabilitation, compensation and restitution. Forms of State Responsibility in Protecting Women Victims of Sexual Violence In terms of Human Rights in Indonesia's Positive Legal System, namely that the State has the responsibility to provide protection and a sense of security to its citizens. In this case, especially for women who are victims of sexual crimes.